Redox Imbalance and Morphological Changes in Skin Fibroblasts in Typical Rett Syndrome. (29th May 2014) - Signorini, Cinzia; Leoncini, Silvia; De Felice, Claudio; Pecorelli, Alessandra; Meloni, Ilaria; Ariani, Francesca; Mari, Francesca; Amabile, Sonia; Paccagnini, Eugenio; Gentile, Mariangela; Belmonte, Giuseppe; Zollo, Gloria; et al.
Abstract : Evidence of oxidative stress has been reported in the blood of patients with Rett syndrome (RTT), a neurodevelopmental disorder mainly caused by mutations in the gene encoding the Methyl-CpG-binding protein 2. Little is known regarding the redox status in RTT cellular systems and its relationship with the morphological phenotype. In RTT patients ( n = 16) we investigated four different oxidative stress markers, F2 -Isoprostanes (F2 -IsoPs), F4 -Neuroprostanes (F4 -NeuroPs), nonprotein bound iron (NPBI), and (4-HNE PAs), and glutathione in one of the most accessible cells, that is, skin fibroblasts, and searched for possible changes in cellular/intracellular structure and qualitative modifications of synthesized collagen. Significantly increased F4 -NeuroPs (12-folds), F2 -IsoPs (7.5-folds) NPBI (2.3-folds), 4-HNE PAs (1.48-folds), and GSSG (1.44-folds) were detected, with significantly decreased GSH (−43.6%) and GSH/GSSG ratio (−3.05 folds). A marked dilation of the rough endoplasmic reticulum cisternae, associated with several cytoplasmic multilamellar bodies, was detectable in RTT fibroblasts. Colocalization of collagen I and collagen III, as well as the percentage of type I collagen as derived by semiquantitative immunofluorescence staining analyses, appears to be significantly reduced in RTT cells. Our findings indicate the presence of a redox imbalance and previously unrecognized morphological skin fibroblast abnormalities in RTT patients.